PENGARUH KELELAHAN DAN STRES KERJA TERHADAP PERAWAT DI RUANG RAWAT INAP RUMAH SAKIT GRANDMED LUBUK PAKAM - Armanda Prima; Ripai Siregar; Muhraza Siddiq; Evfy Septriani Br Ginting; Rizliana Anggita (Fakultas Kesehatan Masyarakat Institut Kesehatan Deli Husada Delitua, 2023)
Fatigue means a gradual decrease in efficiency, work capacity and physical endurance, which affects the ability to maintain necessary activities. Many factors contribute to burnout, including environmental conditions, age, workload, working hours, and stress. Among them, work stress is the main problem in hospital HR management and represents overwhelming pressure from internal and external sources. The research used an analytical observation method and a cross-sectional approach, which allows simultaneous measurement of cause and effect variables in the same context. Notoatmodjo defines a cross-sectional study as the study of the dynamic correlation of risk factors and their effects using observational and data collection techniques at a specific point in time. The findings show that there is a relationship between work fatigue and work stress in Grandmed Lubuk Pakam Hospital Bed Ward in 2022 with a P value of 0.024. In addition, 55% of 22 respondents experienced fatigue, while 30 respondents showed signs of stress.